Learner nurses absenteeism in the nursing schools at Capricorn District, Limpopo Province, South Africa - Thobakgale, E. M.; Lekhuleni, M. E.; Kgole, J. C. (My University, 2013)
This study was designed to determine reasons for learner nurses absenteeism in the nursing schools in Capricorn district, Limpopo Province. A descriptive cross-sectional quantitative design was used to describe factors that contribute to absenteeism of learner nurses in the nursing schools at Capricorn District. The target population consisted of 114 learner nurses at two nursing schools in the Capricorn district. Systematic sampling was used to select 57 learner nurses who participated in the study. Data were collected by means of a self-developed questionnaire comprising 24 items on teaching, content, learning, assessment and social problems. The study revealed that learner nurses were absent from classroom and clinical settings due to shortage of staff in the clinical area, work overload in the clinical area, being treated as workforce, solving their own family problems and being on family responsibility leave. The study recommended that there should be a support system for learner nurses particularly during practical learning in the clinical area.
Published in: African Journal for Physical, Health Education, Recreation and Dance (AJPHERD) March 2013 (Supplement 1), pp. 182-192, Description based on submitted article.
Keywords: Absenteeism; Learner nurses; Nursing schools; Nurses -- South Africa -- Attitudes; Nursing -- Study and teaching -- South Africa